2003
DOI: 10.1076/ceyr.26.4.277.15428
|View full text |Cite
|
Sign up to set email alerts
|

Long term follow-up of retinal nerve fiber layer thickness in eyes with optic nerve head drusen

Abstract: The presence of drusen was found to have no effect on RNFL thickness at follow-up visits. OCT may provide a useful means to evaluate and follow up the RNFL thickness in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 15 publications
(18 reference statements)
1
7
0
Order By: Relevance
“…Subsequent studies yielded the same results [32][33][34]. Unsurprisingly, the current study shows that these two quadrants have a significantly decreased thickness when compared with control eyes, whereas we found no significant difference in the nasal or temporal sectors.…”
Section: Discussionsupporting
confidence: 84%
“…Subsequent studies yielded the same results [32][33][34]. Unsurprisingly, the current study shows that these two quadrants have a significantly decreased thickness when compared with control eyes, whereas we found no significant difference in the nasal or temporal sectors.…”
Section: Discussionsupporting
confidence: 84%
“…16; 32; 48; 62; 74; 88; 92; 103; 141; 153; 154; 158; 170; 201 In a study of OCT RNFL in children with optic disc drusen, Noval et al found the RNFL thickness to be higher than controls in eyes with partially or completely buried drusen and lower than controls in eyes with superficial drusen. 152 The RNFL defect is typically nasal, with sparing of the temporal RNFL.…”
Section: Diagnostic Testingmentioning
confidence: 99%
“…Since Huang et al first described the technology of optical coherence tomography (OCT) over 15 years ago,22 OCT has become a widely-used technology in ophthalmology 3,12,15,16,20. The leading current commercially available OCT machine (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…All of these techniques, however, can only assess if ONHD are present or not; however there is little or no information on the exact shape, size or location of the drusen. Although time domain optical coherence tomography (OCT; StratusOCT, Carl Zeiss Meditec, Dublin, CA) studies have shown not only retinal nerve fiber layer (RNFL) thinning but also documentation of scleral canal size in ONHD patients,7,8,10,15,16 this imaging modality still can not determine exact ONHD size, shape or location, which would be useful when trying to determine if progressive visual field loss is from ONHD or glaucoma.…”
Section: Introductionmentioning
confidence: 99%